Intragastric balloon treatment of obesity must be combined with bariatric surgery: A pilot study in Turkey - Murat SARUÇ,; Deniz BÖLER,; Mehmet KARAARSLAN,; Çağlar BAYSAL,; Kemal RASA,; Metin ÇAKMAKÇI,; Cihan URAS,; Nurdan TÖZÜN, (Turkish Journal of Gastroenterology, 2019)
-